The characteristics of pediatric ulcerative colitis with primary sclerosing cholangitis: A single-center study in Taiwan - Mu-Ming Chien; Mei-Hwei Chang; Kai-Chi Chang; Yu-Chun Chiu; Huey-Ling Chen; Hong-Yuan Hsu; Jia-Feng Wu (Pediatrics and Neonatology)
Background: Primary sclerosing cholangitis (PSC) is often associated with ulcerative colitis (UC). We investigated the clinical characteristics of pediatric UC patients with and without PSC. Methods: We retrospectively recruited children with UC, with and without PSC, from 2006 to 2017 in a tertiary center in Taiwan. The clinical data of the patients, including clinical and endoscopic UC severity scores, medications, and laboratory parameters, were analyzed. Results: We recruited five children with PSC-UC (PSC-UC group), and 26 with UC alone (non-PSC UC group) in this retrospective analysis. Among the patients with PSC-UC, four (80%) were compatible with definite or probable autoimmune sclerosing cholangitis (ASC). The UC Endoscopic Index of Severity (5.00 vs. 9.00, P = 0.003) and Mayo score (4.00 vs. 8.00, P = 0.014) were significantly lower in the PSC-UC group than the non-PSC UC group. The prevalence of immunomodulator use was significantly higher in the PSC-UC than the non-PSC UC group (100% vs. 42.3%, P = 0.043), but there was no difference regarding steroids, mesalamine, or biologics. At the end of the study, significantly fewer patients were steroid-free in the PSC-UC than the non-PSC UC group (20.0% vs. 84.6%, P = 0.010). Conclusions: Pediatric patients with PSC-UC had less severe colitis than those with UC alone in terms of the clinical activity index and endoscopic severity index, but they were more likely to need an immunomodulator and less likely to be steroid-free in the long term, for the control of liver disease.